Antioxidant activity of Momordica charantia extracts - Devi Anggraini Putri; Sri Fatmawati (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
Momordica charantia is one of the herbaceous plants which widely distributed at tropical and subtropical regions. M. charantia, as known as pare, has been used as Indonesian traditional medicine for the treatment of bitter stomachic, laxative, and anthelmintic. This study aims to investigate the antioxidant activity of M. charantia leaves extracts (the n-hexane, dichloromethane, ethyl acetate, and methanol extracts) by using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay. The result showed that the ethyl acetate extract has the highest DPPH scavenging activity with IC50 value of 233.39 μg/mL. Therefore, this study concluded that ethyl acetate extract of M. charantia leaves is recommended as an antioxidant agent.